IT-enabled inter-firm governance model to manage service quality level through customers' feedback. (2015) - Song, Jae H.; Sohn, Changsoo
Internet marketplace providers such as Amazon.com or ebay.com need to control the service quality level of marketplace participants. As a method to control participants, they release customers' feedback for the service that participants provided. This study proposed five learning feedback models using regression analysis of the models on Amazon.com data and found that information disclosure is an effective and significant governing mechanism of the marketplace. Further, Amazon.com has been governed by a combination of partnership, market and contract mechanisms. Collecting customer evaluation based on their volunteerism needs to be complemented by incentive mechanisms and transaction records. For effective combination of the governing mechanisms, more specifically, in order to achieve continuous collaboration with accountability of marketplace participants, information for collaboration, accountability and adaptive learning is needed.